Under siege: virus control in plant meristems and progeny. Issue 8 (20th May 2021) - Bradamante, Gabriele; Mittelsten Scheid, Ortrun; Incarbone, Marco
Abstract: In the arms race between plants and viruses, two frontiers have been utilized for decades to combat viral infections in agriculture. First, many pathogenic viruses are excluded from plant meristems, which allows the regeneration of virus-free plant material by tissue culture. Second, vertical transmission of viruses to the host progeny is often inefficient, thereby reducing the danger of viral transmission through seeds. Numerous reports point to the existence of tightly linked meristematic and transgenerational antiviral barriers that remain poorly understood. In this review, we summarize the current understanding of the molecular mechanisms that exclude viruses from plant stem cells and progeny. We also discuss the evidence connecting viral invasion of meristematic cells and the ability of plants to recover from acute infections. Research spanning decades performed on a variety of virus/host combinations has made clear that, beside morphological barriers, RNA interference (RNAi) plays a crucial role in preventing—or allowing—meristem invasion and vertical transmission. How a virus interacts with plant RNAi pathways in the meristem has profound effects on its symptomatology, persistence, replication rates, and, ultimately, entry into the host progeny. Abstract : We review what is known about the biological mechanisms regulating virus exclusion from—or invasion of—plant host meristems and progeny, including possible consequences and implications of these phenomena.